SOCIALIZATION OF COMMUNITY-BASED EDUCATION QUALITY MANAGEMENT MODEL - Permana, Hinggil; Wahyudin, Undang Ruslan; Nurlailasari, Ella (LPPM Univ. Ibn Khaldun Bogor, 2024)
Pesantren, as the beginning of the original Indonesian educational institution, was only officially recognized legally in 2003 through the National Education System Law Number 20 of 2003. Education in pesantren which initially only focused on mastering religious knowledge, has now begun to integrate general subjects. The inclusion of these subjects aims to broaden the horizons and thoughts of students, often also accompanied by participation in state examinations held by the government. Therefore, it is very appropriate if the pesantren continue to strive to make various improvements and improve the quality and quality of education in pesantren. This study was conducted to evaluate the educational standards applied at Al-Muslih Institute, interviewed was Farid Muhammad M.Pd., who served as principal of Al-Muslih school for 2 years. Pesantren and Al-Muslih Foundation have been established since before 2000, and Al-Muslih Junior High School was established in 2003. Currently, Al-Muslih Junior High School has a total of 126 students and 15 teachers, including the principal and educational staff.